Post-vaccination SARS-CoV-2 neutralizing antibodies in pregnant women receiving biologics for inflammatory bowel disease - Donna E. Leet; Jing Jin; Charles S. Craik; Michael G. Kattah; Millie D. Long; Uma Mahadevan (PLoS ONE, 2025)
Inflammatory bowel disease (IBD) treatments and pregnancy can independently modulate immune responses, but the combined impacts on SARS-CoV-2 vaccine-induced immunity are poorly understood. This study explores the efficacy of SARS-CoV-2 vaccination and placental antibody transfer among pregnant women with IBD on biologic therapies. This observational study included pregnant women with and without IBD from the PIANO and PREVENT-COVID studies and their neonates. We assessed anti-SARS-CoV-2 neutralizing antibody titers (NT50) in maternal and cord blood post-vaccination using a pseudotype neutralization assay and calculated placental transfer ratios. A total of 32 pregnant women participated, and 27 were exposed to a biologic medication during pregnancy. Neutralizing antibody titers were similar between biologic-treated and non-treated groups, and biologic-exposed women demonstrated robust placental transfer of neutralizing antibodies. Corticosteroid use during pregnancy was significantly associated with reduced placental transfer efficiency, although this effect was not significant in a sensitivity analysis excluding patients treated with immunomodulators. Vaccination timing and SARS-CoV-2 infection impacted maternal and cord antibody levels, with higher titers observed in those vaccinated before pregnancy or infected during pregnancy. Overall, our findings suggest that upon vaccination, pregnant women with IBD on biologic therapies mount effective SARS-CoV-2 neutralizing antibody responses similar to their non-biologic-exposed counterparts, with efficient placental transfer. These findings support the efficacy of SARS-CoV-2 vaccination in this population, though further research with larger cohorts is needed for validation and to explore the long-term protective effects of transferred antibodies in neonates. Furthermore, corticosteroid use, immunomodulator use, and vaccination timing may influence antibody dynamics, underscoring the need for tailored clinical management in this vulnerable population.